P14.04 10 years of weekly web conference for brain tumor of Adolescent/Young Adult (AYA) on behalf of ANOCEF, GO-AJA and SFCE societies. (6th September 2019) - Frappaz, D; Bronnimann, C; Faure Conter, C; Vauleon, E; Meyronnet, D; Sunyach, M; Leblond, P; Tanguy, R; Laurence, V; Bonneville-Levard, A
Abstract: BACKGROUND: The skills of adult versus pediatric neuro-oncologists are not completely similar though additive. Because the tumors and their protocols are different and the tolerance and expected sequelae are specific. Multidisciplinary meetings including adult and pediatric neuro oncologists are warranted to share expertise. MATERIAL AND METHODS: Since 2008, on behalf of ANOCEF, GO-AJA and SFCE societies, a weekly national web based conference was held in France. Any patient with the following criteria could be discussed: Adolescent and Young Adults aged between 15 and 25 years, and any adult with a pediatric type pathology, including medulloblastoma, germ cell tumors, embryonic tumors, ependymoma, pilocytic astrocytoma. RESULTS: Number of cases discussed increased from 8 to 202/year, with a mean number of 3 cases (1 to 7) discussed at each meeting. In 2018, 36 meetings were held, with a mean of 8 participants (2 to 14) issued from various French centers. 168 cases were discussed in 2018. Mean age was 30 years old (7 to 67). 45% were discussed at diagnosis; The patients had mostly medulloblastomas (n=47), ependymomas (n=24), low (n=21) or high grade gliomas (n=11), pineal tumors (n=20), germ cell tumors (n=9) and embryonal tumors (n=6). The rate of inclusion in protocols was increased since the opening of this web conference, especially for the germ cell tumor GCT SIOP protocol that is opened without age restriction, and in RSMA standard risk or MEVITEM relapse adult medulloblastoma protocols. CONCLUSION: Multidisciplinary Web conference for AYAs is feasible and fruitful. It shares knowledge and increases the inclusion rate in protocols. It should be developped further.